2018
DOI: 10.1002/zaac.201800121
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐inspired Oxidation of 1‐Aminocarboxylic Acids by a Nonheme Iron(II) Complex: Mimicking the Activity of 1‐Aminocyclopropane‐1‐carboxylic Acid Oxidase

Abstract: Three new ternary iron(II) complexes, [(TpPh2)FeII(ACC)] (1), [(TpPh2)FeII(ACH)] (2), and [(TpPh2)FeII(ADP)] (3) [TpPh2 = hydrotris(3,5‐diphenylpyrazol‐1‐yl)borate, ACC‐H = 1‐aminocyclopropane‐1‐carboxylic acid, ACH‐H = 1‐aminocyclohexane‐1‐carboxylic acid, and ADP‐H = 2‐amino‐2,2‐diphenylacetic acid] were isolated and characterized. X‐ray crystal structures of 1 and 2 reveal that in both the complexes the TpPh2 ligand binds to the central iron atom in a facial mode, and the respective 1‐aminocarboxylate monoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It is worth noting that to the best of our knowledge, this is the first example in which a heterogeneous catalyst is used to produce ethylene from ACC. Indeed, all the previously reported studies have been focused on the use of iron and copper , complexes as homogeneous catalysts. Moreover, other hybrid/ACC/H 2 O 2 molar ratios (1:10:10, 1:20:20, and 1:100:100) were also tested with the aim of confirming if smaller amounts of HA@MIL-100­(Fe) could efficiently degrade ACC into ethylene gas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that to the best of our knowledge, this is the first example in which a heterogeneous catalyst is used to produce ethylene from ACC. Indeed, all the previously reported studies have been focused on the use of iron and copper , complexes as homogeneous catalysts. Moreover, other hybrid/ACC/H 2 O 2 molar ratios (1:10:10, 1:20:20, and 1:100:100) were also tested with the aim of confirming if smaller amounts of HA@MIL-100­(Fe) could efficiently degrade ACC into ethylene gas.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in plants, the conversion of the precursor 1-aminocyclopropane-1-carboxylic acid (ACC) to ethylene is catalyzed by the ACC-oxidase (ACCO) protein in the presence of oxygen, ascorbic acid, Fe­(II), and hydrogen carbonate . It is worth noting, it has been already demonstrated that some Fe­(II) or Fe­(III) complexes can also catalyze the degradation of ACC to ethylene gas, mimicking the enzymatic activity of ACCO. However, ethylene production from these iron complexes has been investigated mainly in organic solvents, which limits the practical application of the above-mentioned compounds. Consequently, the search for alternative biomimetic ACCO like systems is of high interest.…”
Section: Introductionmentioning
confidence: 99%